Roald Dahl Little Library. 2, Creatures - Dahl, Roald (Puffin Books, 2019)
Learn whizzpopping creatures for all littlôe chiddlers from the world of Roald Dahl. A delightful treat for curious little hands, this little library is perfect for introducing titchy toddlers to new concepts, and to the imaginative world of Roald Dahl.